China's urban ideology: new towns, creation cities, and contested landscapes of memory. Issue 4 (4th July 2019) - Oakes, Tim
ABSTRACT: This paper argues that "the urban" has emerged as the most significant ideological realm in contemporary China. In developing this argument, I suggest an alternative approach to how we theorize urbanization in China. Seeking to avoid the dichotomized analyses that often characterize scholarship on China's urbanization, the paper suggests reading "the urban" as an ideological device. Such a reading calls for an analytical distinction between the city as a technology of socialist party-state planning and government and urbanization as a messy social process over which the state struggles for control. It also calls for a recognition of the ways that ideology itself has shifted dramatically in China, from the Mao-era centrality and coherence of class struggle and its overriding goal of proletarianization to a much less coherent post-reform message of "stability". The paper begins with a brief discussion of ideology and Gramsci's notion of "common sense" in a Chinese register. It then considers the film 24 City, directed by Jia Zhangke, as a template for understanding urban spaces as sites of conflict between the city as an ideological device and urbanization as a social process. New urban spaces are then explored in an effort to tease out their complex and contradictory ideological renderings. I conclude with an argument about the openness and contradictions of China's urban spaces and how an ideological analysis can resist the kind of theoretical closure that much work on urbanization in China seems to aim for.